SOSIALISASI DAN PELATIHAN PENANAMAN HIDROPONIK DI WILAYAH PERKOTAAN DALAM RANGKA PERGERAKAN URBAN FARMING DI SEMANGGI PASAR KLIWON SURAKARTA - Fitrianingtyas, Anjar; Aninda Hikmatiar; Aura Permata Mulia; Ayu Safitri; Azizah Nur Amalina; Desi Mariani; Erizal Nur Pamungkas; Nada Indie Kharisma; Penta Lavida; Revanna Farnesia; Setyo Ranu Murti (Nusantara Hasana Journal, 2022)
This community service activity aims to educate the public regarding hydroponic planting to support the concept of urban farming in urban areas. This activity was initiated by the UNS KKN Team Group 14 Semanggi 2022. The method of activity used in this service activity is simulation and practice of technical training and basic knowledge of hydroponic installations with the aim that people can know the use of hydroponics and develop hydroponics so that it becomes a selling point. Knowledge of hydroponics can improve the atmosphere of doing work that is fun, creative and innovative. The results of the activities achieved are in the form of the community implementing individual hydroponic making and utilizing used materials found around the RW 01 environment to be used as planting media for vegetable cultivation by means of hydroponic cultivation. These activities are expected to be the basis for entrepreneurial development for the surrounding community.